Dynamic Provisioning for Community Services - Qi, Li; Jin, Hai (Advanced Topics in Science and Technology in China, 2013)
Dynamic Provisioning for Community Services outlines a dynamic provisioning and maintenance mechanism in a running distributed system, e.g. the grid, which can be used to maximize the utilization of computing resources and user demands. The book includes a complete and reliable maintenance system solution for the large-scale distributed system and an interoperation mechanism for the grid middleware deployed in the United States, Europe, and China. The experiments and evaluations have all been practically implemented for ChinaGrid, and the best practices established can help readers to construct reliable distributed systems.   This book is intended for researchers, developers, and graduate students in the fields of grid computing, service-oriented architecture and dynamic maintenance for large distributed systems.   Li Qi is an Associate Professor and the Deputy Director of the R&D Center for the Internet of Things at the Third Research Institute of Ministry of Public Security (TRIMPS), China. Hai Jin is a Professor and the Director of Department of Computer Science, Huazhong University of Science and Technology, China.